Legal Construction of the Fulfillment of Social Security Rights for Freelance Workers - Harmono, Harmono; Gumilang , Iwan G; Sahila , Fatina Rizka; Khoerunnisa, Anis; Risfanda , Muhammad Ivan (Journal of Legal and Cultural Analytics, 2025)
The increasing number of freelancers in Indonesia, particularly among Millennials and Generation Z, reflects a shift in employment trends toward more flexible work arrangements. However, these workers, mostly part of the informal labor sector, often do not receive adequate legal protection, especially regarding social security and labor rights. Despite their significant contributions to the digital economy and various industries, freelancers still face legal uncertainty due to the absence of specific regulations that obligate employers to fulfill their responsibilities. This study examines the legal framework governing freelancers' rights in Indonesia, focusing on Law No. 24 of 2011 concerning the Social Security Administrative Body (BPJS) and Government Regulation No. 35 of 2021. Methods, Using a normative juridical research method, this study analyzes laws, legal principles, and the effectiveness of sanctions imposed on employers who neglect their obligations.  The results reveal that existing laws do not explicitly include freelancers in the category of workers entitled to social security, and the administrative sanctions are insufficient to ensure compliance. The study recommends revising the legal framework to regulate freelancers' rights explicitly and impose stricter penalties on non-compliant employers. Implementation. Such changes are essential to ensure legal certainty, justice, and social protection in Indonesia's evolving labor market.